"Awakening the mother mind": Exploring the relationship between ego and the climate crisis - Rapitsenyane, Duduetsang B. (HTS teologiese studies, 2023)
As Vuzamazulu Credo Mutwa, a South African sangoma, gave his message to the world, he urged human beings to awaken the mother mind within them. He pleaded with human beings to let go of the warrior mind and start thinking like mothers and grandmothers. This article aimed to elaborate on Credo’s short and mystical message. The article interprets the warrior mind to be the masculine mind, while the mother mind is perceived as representing the feminine mind. Ego works well with the warrior or masculine mind, and is not so compatible with the feminine mind. The argument is that ego and the climate crisis are inextricably linked, and that diminishing the ego will leave the Earth and its inhabitants with a high chance of survival. Furthermore, it is illustrated how colonialism and institutions like religion exacerbate egoism in the world. The ego is defined, its growth origins traced, and its effects on the Earth highlighted. Finally, the article concludes by suggesting how to diminish ego and awaken the mother mind within every one of us. Secondary data analysis method is used throughout the article.Contribution: This article applies existing and timeless ideas to figure out solutions to the climate crisis. It also analyses gender issues through the lenses of analytical psychology. Different disciplines are applied to explore the concept of the ‘mother mind’. It is unique in that it places the burden on the individual, stressing that the solutions are found within an individual.